Immunohistochemistry in Investigative and Toxicologic Pathology. (July 2018) - Janardhan, Kyathanahalli S.; Jensen, Heather; Clayton, Natasha P.; Herbert, Ronald A.
Immunohistochemistry (IHC) is a valuable tool in pathology. This review provides a brief description of the technical aspects of IHC and a detailed discussion on the variables that affect the results, interpretation, and reproducibility of IHC results. Lists of antibodies that have and have not worked in IHC on various mouse and rat tissues in our laboratory are provided as a guidance for selection of antibodies. An approach to IHC method optimization is presented. Finally, the critical information that should be included as a part of peer-reviewed manuscript is also discussed.